CAMKK2 promotes prostate cancer independently of AMPK via increased lipogenesis - Penfold,L; Woods,A; Muckett,P; Nikitin,A; Kent,T; Zhang,S; Graham,R; Pollard,A; Carling,D (Cancer Research, 2018)
New targets are required for treating prostate cancer, particularly castrate-resistant disease. Previous studies reported that calcium/calmodulin-dependent protein kinase kinase 2 (CAMKK2) expression is increased in human prostate cancer. Here, we show that Camkk2 deletion or pharmacologic inhibition protects against prostate cancer development in a preclinical mouse model that lacks expression of prostate-specific Pten. In contrast, deletion of AMP-activated protein kinase (Ampk) β1 resulted in earlier onset of adenocarcinoma development. These findings suggest for the first time that Camkk2 and Ampk have opposing effects in prostate cancer progression. Loss of CAMKK2 in vivo or in human prostate cancer cells reduced the expression of two key lipogenic enzymes, acetyl-CoA carboxylase and fatty acid synthase. This reduction was mediated via a posttranscriptional mechanism, potentially involving a decrease in protein translation. Moreover, either deletion of CAMKK2 or activation of AMPK reduced cell growth in human prostate cancer cells by inhibiting de novo lipogenesis. Activation of AMPK in a panel of human prostate cancer cells inhibited cell proliferation, migration, and invasion as well as androgen-receptor signaling. These findings demonstrate that CAMKK2 and AMPK have opposing effects on lipogenesis, providing a potential mechanism for their contrasting effects on prostate cancer progression in vivo. They also suggest that inhibition of CAMKK2 combined with activation of AMPK would offer an efficacious therapeutic strategy in treatment of prostate cancer.